Active surveillance documents rates of clinical care seeking due to respiratory illness. Issue 5 (16th May 2020) - Galanti, Marta; Comito, Devon; Ligon, Chanel; Lane, Benjamin; Matienzo, Nelsa; Ibrahim, Sadiat; Shittu, Atinuke; Tagne, Eudosie; Birger, Ruthie; Ud‐Dean, Minhaz; Filip, Ioan; Morita, Haruka; et al.
Abstract: Background: Respiratory viral infections are a leading cause of disease worldwide. However, the overall community prevalence of infections has not been properly assessed, as standard surveillance is typically acquired passively among individuals seeking clinical care. Methods: We conducted a prospective cohort study in which participants provided daily diaries and weekly nasopharyngeal specimens that were tested for respiratory viruses. These data were used to analyze healthcare seeking behavior, compared with cross‐sectional ED data and NYC surveillance reports, and used to evaluate biases of medically attended ILI as signal for population respiratory disease and infection. Results: The likelihood of seeking medical attention was virus‐dependent: higher for influenza and metapneumovirus (19%‐20%), lower for coronavirus and RSV (4%), and 71% of individuals with self‐reported ILI did not seek care and half of medically attended symptomatic manifestations did not meet the criteria for ILI. Only 5% of cohort respiratory virus infections and 21% of influenza infections were medically attended and classifiable as ILI. We estimated 1 ILI event per person/year but multiple respiratory infections per year. Conclusion: Standard, healthcare‐based respiratory surveillance has multiple limitations. Specifically, ILI is an incomplete metric for quantifying respiratory disease, viral respiratory infection, and influenza infection. The prevalence of respiratory viruses, as reported by standard, healthcare‐based surveillance, is skewed toward viruses producing more severe symptoms. Active, longitudinal studies are a helpful supplement to standard surveillance, can improve understanding of the overall circulation and burden of respiratory viruses, and can aid development of more robust measures for controlling the spread of these pathogens.